Advanced Enterprise Architecture Credit Card Contact Center Service in Bank XYZ Using TOGAF Framework - Hans Kristian, Stefan G. Bunawan, Firman Pangemanan, Emil R. Kaburuan, Tuga Mauritsus (International Journal of Advanced Science and Technology, 2020)
Bank XYZ as one of the finance institutions has many products of their services and one of the biggest customers come from Credit Card Customers. To ensure the service for the credit card customers easier and quicker and better, the Contact center Service for credit card established. This contact center must receive incoming Customer Complaints and provide outgoing solutions to the customer complaints. In order to fulfill the business strategy, Enterprise Architecture for the IS/IT of Credit Card Contact center needs to be improved. Research offer the improvement assessment of the enterprise architecture by the study literature of TOGAF Framework. Keywords: Institution, Credit Card Customers, Contact center Service, Customer Complaints, Enterprise Architecture, TOGAF Framework